The Effect of Project Based Learning Models and Learning Motivation on Civics Learning Results in 4th Grade Primary School 106163 Percut Sei Tuan - Luciana Simanjuntak; Sriadhi Sriadhi; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to: (1) Determine the differences in student PPKn learning outcomes taught with a project-based learning model compared to students taught using a direct learning model; (2) Knowing the differences in the learning outcomes of students who have high learning motivation compared to students who have low learning motivation; (3) Knowing the interaction between the project based learning model and learning motivation in influencing the learning outcomes of students' PPKn at Primary School 106163 Percut Sei Tuan. The population in this study were the fourth grade students at Primary School 106163 Percut Sei Tuan, totaling 54 people. 4th Grade a as many as 27 students and 4th Grade / b as many as 27 students. Collecting data in this study through a questionnaire on learning motivation and learning outcomes test instruments PPKn. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1) The PPKn learning outcomes of students who were taught with the project based learning model were higher than the PPKn learning outcomes of students taught using the direct learning model (Fcount= 23.476 and the sig. 0.000> 0.05); (2) Student PPKn learning outcomes who have high learning motivation are higher than those with PPKn learning outcomes of students who have low learning motivation (Fcount = 7.673 and sig. 0.008> 0.05); (3) There is an interaction between the project based learning model and learning motivation in influencing students' PPKn learning outcomes (Fcount = 13.003 and sig. 0.001> 0.05).